Preparation method and application of rice hull based nanocomposite ZnFe2O4 / C / SiO2

The preparation of ZnFe2O4/C/SiO2 nanocomposites through rice husk support solves the problems of tetracycline hydrochloride pollution and catalyst agglomeration in water, achieves efficient degradation and material recycling, and has good environmental friendliness and sustainability.

CN119822416APending Publication Date: 2025-04-15QUANZHOU NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510102371.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the pollution of tetracycline hydrochloride in water bodies, and ZnFe2O4 nanoparticles are prone to agglomeration during the reaction process, reducing catalytic performance.

Method used

ZnFe2O4/C/SiO2 nanocomposites are prepared by rice husks as support. Through ultrasonic treatment, hydrothermal reaction and other steps, the dispersion and catalytic activity of the material are improved, and are used to degrade tetracycline hydrochloride using microwaves.

Benefits of technology

It has achieved efficient removal of tetracycline hydrochloride in water, with a degradation rate of up to 99.11%, and the materials are recovered through magnetic separation, reducing production costs and environmental burden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822416A_ABST
    Figure CN119822416A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a rice hull based nano composite material ZnFe2O4 / C / SiO2 and an application of the rice hull based nano composite material ZnFe2O4 / C / SiO2 in degradation of tetracycline hydrochloride (TCH). According to the method, waste rice husks are taken as main raw materials, a mixed solution of ferric salt and zinc salt is introduced, and the ZnFe2O4 / C / SiO2 nano composite material is prepared by adopting a hydrothermal method. The material shows excellent performance in the aspect of TCH degradation, meanwhile, efficient recovery and cyclic utilization of the catalyst can be achieved, and secondary pollution is avoided. In addition, the method provides a new thought for efficient utilization and resource conversion of the rice hull waste, and has both environmental friendliness and economical efficiency. Meanwhile, microwave reaction conditions are mild, efficient degradation can be achieved under normal pressure, energy consumption and operation complexity are remarkably reduced, the ideas of greenization and sustainable development are fully embodied, and good application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of novel bio-based functional materials and environmental pollution control, and specifically relates to a preparation method and application of a rice husk-based nanocomposite material ZnFe2O4 / C / SiO2. Background Art

[0002] With the rapid development of industry and agriculture, the discharge of organic pollutants in wastewater has posed a serious threat to the environment. Among them, tetracycline hydrochloride (TCH) has been widely used in animal husbandry and aquaculture due to its broad-spectrum antibacterial properties and low economic cost. However, since TCH is difficult to be completely absorbed during use, its metabolites and even original molecules are directly discharged into the environment, causing water pollution and gradually becoming one of the main organic pollutants in environmental water bodies. Therefore, the development of efficient and stable technical means to remove TCH from water bodies has become a key research topic in the current field of water pollution control.

[0003] Microwave-induced (MW) catalytic technology has been widely used in various wastewater treatment fields due to its advantages of low energy consumption, short reaction time and high degradation efficiency. One of the core advantages of MW technology is its high adjustability, which can be precisely controlled by externally controlled microwave power. However, the efficiency of MW catalytic degradation is highly dependent on the characteristics of the selected catalyst, especially catalysts with high microwave selectivity, which can significantly improve the degradation performance. Studies have shown that the catalytic decomposition of harmful organic pollutants can be significantly accelerated by combining MW radiation with MW absorbing materials such as activated carbon, polymers, carbon nanotubes (CNTs), transition metal oxides, and ferromagnetic metal powders. Among the many MW absorbing materials, ZnFe2O4 shows good application potential due to its high cost-effectiveness and easy preparation. However, due to the high surface energy of ZnFe2O4 nanoparticles, they are prone to agglomeration during the reaction, resulting in a reduction in reaction sites and a significant reduction in catalytic performance. To solve this problem, inert inorganic materials such as alumina, mesoporous silica, and montmorillonite are usually used as carriers of nanocatalysts to improve dispersion and enhance their catalytic activity.

[0004] Rice husk is a common agricultural waste, rich in inert silica and biochar resources, but the current utilization rate is low. Traditional treatment methods of rice husk, such as incineration, landfill and dumping, not only waste resources, but also may cause secondary pollution to the environment. Therefore, the present invention aims to solve how to reasonably utilize rice husk as a resource to solve the agglomeration of ZnFe2O4 nanoparticles and improve the catalytic activity of the material. Summary of the invention

[0005] In view of the deficiencies of the prior art, the present invention provides a method for preparing a rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 and its application in microwave degradation of tetracycline hydrochloride. The ZnFe2O4 / C / SiO2 nanocomposite material prepared by the method has an easily accessible raw material source, a simple preparation process and required equipment, and the material itself is environmentally friendly, pollution-free, and has low production cost. In addition, the composite material has mild reaction conditions during the degradation process, and can achieve efficient degradation under normal pressure conditions without the need for a high-pressure environment.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is: A method for preparing a rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 comprises the following steps: (1) Pretreatment of rice husk: Place the rice husk in clean water for ultrasonic treatment, then wash it with clean water and ultrapure water for 3 to 5 times respectively, and dry it to constant weight to obtain dry rice husk; (2) Preparation of rice husk carbon: The dry rice husk obtained in step (1) is carbonized to obtain rice husk carbon, and the rice husk carbon is then calcined together with KOH in a tube furnace. The obtained product is treated with hydrochloric acid to remove metal impurities, and washed to neutrality to obtain C / SiO2; (3) Pretreatment of the nanocomposite material: immersing the C / SiO2 obtained in step (2) in an iron salt solution, then adding a zinc salt solution, mixing the above solution thoroughly by ultrasonication, and then adding sodium acetate as a precipitant; (4) Preparation of ZnFe2O4 / C / SiO2 nanocomposite material: The solution obtained in step (3) is placed in a stainless steel autoclave for hydrothermal reaction. The final product is washed and dried multiple times to obtain a ZnFe2O4 / C / SiO2 nanocomposite material.

[0007] Furthermore, the carbonization step in step (2) is to place the dry rice husk into a porcelain boat and transfer it to a tube furnace for calcination, with nitrogen at a rate of 250 ml·min -1 The flow rate of nitrogen was continuously flowed into the tube furnace for 1 h to remove air; then the nitrogen flow rate was reduced to 150 ml min -1 , increase the furnace temperature to 700 ℃ at a heating rate of 5 ℃ / min and maintain it for 2 h.

[0008] Furthermore, in step (2), the mass ratio of rice husk carbon to KOH is 1:1; the specific step of calcination is to place the rice husk carbon and KOH in a tube furnace for calcination, and nitrogen is saturated at 250 ml·min -1 The flow rate of nitrogen was continuously allowed to flow into the tube furnace for 1 h to remove air, and then the nitrogen flow rate was reduced to 150 ml min -1 , increase the furnace temperature to 750 ℃ ​​at a heating rate of 5 ℃ / min and hold for 1 h.

[0009] Furthermore, the concentration of the hydrochloric acid in step (2) is 2 mol / L, and the treatment is carried out under magnetic stirring at 500 rpm.

[0010] Furthermore, in step (3), the ratio of C / SiO2 to the iron salt solution is 0.5 g:35 mL; the concentration of the iron salt solution is 8 mol / L, and the iron salt is selected from ferric chloride hexahydrate; the concentration of the zinc salt solution is 4 mol / L, and the zinc salt is selected from zinc chloride, and the concentration ratio of the iron salt to the zinc salt is 2:1.

[0011] Furthermore, the amount of sodium acetate used in step (3) is 3.2 g.

[0012] Furthermore, the temperature of the hydrothermal reaction in step (4) is 200°C and the reaction time is 15 h.

[0013] The present invention also provides a rice husk-based nano composite material ZnFe2O4 / C / SiO2 obtained by the preparation method.

[0014] The present invention also provides application of the rice husk-based nano composite material ZnFe2O4 / C / SiO2 in microwave degradation of tetracycline hydrochloride.

[0015] Furthermore, the dosage of the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 is 50-150 mg; and the power of the microwave is 100-1000 w.

[0016] Compared with the prior art, the present invention has the following significant advantages and beneficial effects: (1) Resource utilization and cost advantages: The nanomaterials used in the present invention use waste rice husks as carriers, and the raw materials are widely available and low-cost. This method not only avoids the environmental pollution problems that may be caused by traditional treatment methods, but also achieves efficient recycling and resource utilization of agricultural waste, and has good environmental friendliness and sustainability.

[0017] (2) Pollution prevention and control and material performance advantages: The present invention effectively solves the problem of difficulty in recovering metal ions in catalysts and the problem of secondary pollution. The prepared nanomaterials have the characteristics of simple preparation process and stable chemical properties, which significantly improves the reliability and safety of their practical applications.

[0018] (3) Degradation efficiency and ease of operation: The microwave degradation of tetracycline hydrochloride (TCH) is achieved by using nanocomposite materials. The method of the present invention is simple to operate and has a fast reaction. The removal rate of TCH in the present invention is as high as 99.11%, reflecting excellent degradation performance.

[0019] (4) Magnetic separation and recovery performance: The nanocomposite material prepared by the present invention has excellent magnetic separation effect, is non-toxic, efficient and stable. After the catalytic reaction is completed, the material can be easily recovered by magnetic separation, thus realizing the recycling of the material and further reducing the use cost and environmental burden.

[0020] (5) Optimization of preparation process and conditions: The materials required for the present invention are easy to obtain, the preparation process is simple, the equipment requirements are low, and the reaction conditions are mild. No harsh experimental environment is required, which provides convenient conditions for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 (a) is the SEM image of activated porous rice husk carbon (C / SiO2), (b) is ZnFe2O4, and (c) is the ZnFe2O4 / C / SiO2 nanocomposite material.

[0022] Figure 2 Schematic diagram of the specific surface area and pore size of rice husk carbon.

[0023] Figure 3 This is a comparison chart of the degradation rates of tetracycline hydrochloride in microwave degradation with different added amounts of ZnFe2O4 / C / SiO2 nanocomposites.

[0024] Figure 4 Comparison of the effects of different microwave powers on tetracycline degradation rate.

[0025] Figure 5 Comparison of the effects of no material, ZnFe2O4 and ZnFe2O4 / C / SiO2 nanocomposite materials on the degradation rate of tetracycline hydrochloride.

[0026] Figure 6 The degradation rate of tetracycline hydrochloride by ZnFe2O4 / C / SiO2 nanocomposite material after four cycles of use. DETAILED DESCRIPTION

[0027] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0028] The preparation process of FeCl3·6H2O solution and ZnCl2 solution in the following examples and comparative examples is as follows: Under continuous magnetic stirring, FeCl3·6H2O and ZnCl2 are respectively dissolved in 30 mL of ethylene glycol to prepare 8 mol / L FeCl3·6H2O solution and 4 mol / L ZnCl2 solution, and the obtained solutions are ultrasonically treated at 600 W for 1 hour to ensure complete dispersion.

[0029] Example 1 1. Preparation of ZnFe2O4 / C / SiO2 nanocomposite materials: (1) Pretreatment of rice husk: After ultrasonic treatment of rice husk in clean water, wash it three times with clean water and ultrapure water respectively, and dry it to constant weight to obtain dry rice husk for later use.

[0030] (2) Preparation of rice husk carbon (C / SiO2): Dried rice husk was placed in a porcelain boat and transferred to a tube furnace for calcination. Nitrogen was used at a rate of 250 ml min -1 The nitrogen flow rate was then reduced to 150 ml min -1 The furnace temperature was raised to 700 °C at a heating rate of 5 °C / min and maintained for 2 h. The rice husk carbon and KOH were then placed in a tubular furnace for calcination activation at a mass ratio of 1:1, and nitrogen was introduced at a rate of 250 ml·min -1 The nitrogen flow rate was then reduced to 150 ml min -1 The furnace temperature was raised to 750 °C at a heating rate of 5 °C / min and maintained for 1 h. The obtained carbonized product was mixed with 2 mol / L hydrochloric acid solution, stirred at 500 rpm to remove metal impurities, washed with deionized water until neutral, dried in an oven to constant weight, and ground to obtain C / SiO2. The specific surface area of ​​the obtained C / SiO2 was 817.70 m 2 / g, pore size 2.85 nm ( Figure 2 ).

[0031] (3) Pretreatment of nanocomposites: 0.5 g C / SiO2 was immersed in 35 mL FeCl3·6H2O solution (concentration: 8 mol / L), followed by the slow addition of 35 mL ZnCl2 solution (4 mol / L). The mixture was treated under 600 W ultrasound and vigorous stirring (speed: 1000 rpm) for 1 h. 3.2 g sodium acetate was added as a precipitant to promote the reaction.

[0032] (4) Preparation of ZnFe2O4 / C / SiO2 nanocomposite materials: The homogenized solution was placed in a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and subjected to hydrothermal reaction at 200 °C for 15 h. After the reaction, the product was filtered and washed with ethanol and deionized water for 3 to 5 times and then dried to obtain ZnFe2O4 / C / SiO2 nanocomposite materials.

[0033] Figure 1 a is the SEM image of activated porous rice husk carbon (C / SiO2), Figure 1 b is the SEM image of ZnFe2O4, Figure 1 c is the SEM image of ZnFe2O4 / C / SiO2 nanocomposite carbon.

[0034] 2. Application of ZnFe2O4 / C / SiO2 nanocomposites in microwave degradation of TCH: (1) Prepare 60 mg / L TCH aqueous solution and stir until uniform.

[0035] (2) Take 50 mL of TCH solution (60 mg / L), add 75 mg of the ZnFe2O4 / C / SiO2 nanocomposite material in Example 1, and irradiate the solution under microwave conditions of 500 W. The degradation of TCH is tested every 3 minutes, and a TCH degradation diagram is obtained, thereby calculating that the TCH degradation rate after 21 minutes of microwave irradiation is 94.1%.

[0036] Example 2 The difference between this embodiment and embodiment 1 is that the amount of ZnFe2O4 / C / SiO2 nanocomposite material used in microwave degradation of TCH is different. In this embodiment, 50 mg of ZnFe2O4 / C / SiO2 nanocomposite material is added, and the other steps are the same as those in embodiment 1. The degradation of TCH is tested every 3 minutes, and a TCH degradation diagram is obtained, thereby calculating that the TCH degradation rate after microwave radiation for 21 minutes is 91.4%.

[0037] Example 3 The difference between this embodiment and embodiment 1 is the amount of ZnFe2O4 / C / SiO2 nanocomposite material used in microwave degradation of TCH. In this embodiment, 100 mg of ZnFe2O4 / C / SiO2 nanocomposite material is added, and the other steps are the same as those in embodiment 1. The degradation of TCH is tested every 3 minutes, and a TCH degradation diagram is obtained, thereby calculating that the TCH degradation rate after 21 minutes of microwave radiation is 96.5%.

[0038] Example 4 The difference between this embodiment and embodiment 1 is the amount of ZnFe2O4 / C / SiO2 nanocomposite material used in microwave degradation of TCH. In this embodiment, 150 mg of ZnFe2O4 / C / SiO2 nanocomposite material is added, and the other steps are the same as those in embodiment 1. The degradation of TCH is tested every 3 minutes, and a TCH degradation diagram is obtained, thereby calculating that the TCH degradation rate after microwave radiation for 21 minutes is 99.1%.

[0039] After the reaction, the solution containing the ZnFe2O4 / C / SiO2 nanocomposite material was separated by an external magnetic field to recover the nanocomposite material. The recovered composite nanomaterial was washed with ethanol and deionized water and vacuum dried at 60°C to obtain a regenerated ZnFe2O4 / C / SiO2 nanocomposite material. The regenerated ZnFe2O4 / C / SiO2 nanocomposite material was used for TCH degradation. After four times of recycling, the removal rate of TCH was still 68.8%.

[0040] Example 5 The difference between this embodiment and embodiment 3 is that the power of microwave radiation used in the microwave degradation of TCH by ZnFe2O4 / C / SiO2 nanocomposite material is different, so as to more clearly understand the effect of different microwave powers on the degradation rate of TCH. The other steps are the same as those in embodiment 1.

[0041] Application of ZnFe2O4 / C / SiO2 nanocomposite materials in microwave degradation of TCH: (4) Prepare a 60 mg / L TCH solution, stir until uniform, take 50 mL of the above TCH solution, add 100 mg of ZnFe2O4 / C / SiO2 nanocomposite material, and irradiate under microwave power conditions of (100, 200, 500 and 1000 W). The degradation of TCH was tested every 3 minutes, and a TCH degradation diagram was obtained, thereby calculating the TCH degradation rate under microwave irradiation for 21 minutes.

[0042] Comparative Example 1 Synthesis steps of ZnFe2O4: (1) Under vigorous stirring (1000 rmp), 3.2 g of sodium acetate (CH3COONa) was introduced into the homogeneous mixture as a precipitant to promote the formation of the final product. The obtained homogeneous reaction solution was sealed in a 100 mL Teflon-lined stainless steel autoclave and maintained at 200 °C for 15 h.

[0043] (2) The obtained precipitate was washed three times with ethanol and then three times with deionized water. After each washing step, the suspension was centrifuged to separate the solid product to obtain ZnFe2O4.

[0044] At the same time, the effects of not adding any materials, adding ZnFe2O4 and ZnFe2O4 / C / SiO2 nanocomposites on the degradation rate of 150 mL tetracycline hydrochloride (TCH) were investigated (the addition amount was 100 mg and the power was 500 w).

[0045] Figure 2 Schematic diagram of the specific surface area and pore size of rice husk carbon.

[0046] Figure 3 The figure shows the effect of different addition amounts of ZnFe2O4 / C / SiO2 nanocomposites on the degradation rate during microwave degradation of tetracycline hydrochloride (TCH) in Example 1, Example 2, Example 3 and Example 4. It can be observed from the figure that the degradation rate of TCH also increases with the increase of the amount of catalyst, showing a positive correlation with the amount of catalyst. When the amount of catalyst reaches 150 mg, the degradation rate of TCH is further increased to 99.1%.

[0047] Figure 4 The figure is a comparison of the effects of different microwave powers on the degradation rate of tetracycline hydrochloride (TCH) in Example 5. As the microwave power increases, the degradation efficiency of the material can be improved. Under the same tetracycline hydrochloride (TCH) concentration conditions, as the microwave power gradually increases, the degradation rate of TCH is significantly accelerated. When the microwave power reaches 1000 W, the removal rate of TCH is as high as 98.5%.

[0048] Figure 5 Pure microwave (no added materials) 、 Comparison of the effects of ZnFe2O4 and ZnFe2O4 / C / SiO2 nanocomposites on the degradation rate of tetracycline hydrochloride (TCH). The results show that compared with microwave alone and ZnFe2O4 without C / SiO2 loading, the ZnFe2O4 / C / SiO2 nanocomposites synthesized in the present invention have the best effect in degrading tetracycline.

[0049] Figure 6 This is the result graph of the degradation rate of tetracycline hydrochloride (TCH) after four cycles of use of ZnFe2O4 / C / SiO2 nanocomposite materials. The degradation rate is 68.82% after four cycles.

[0050] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing a rice husk-based nanocomposite material ZnFe2O4 / C / SiO2, characterized in that: The following steps are involved: (1) Pretreatment of rice husk: Place the rice husk in clean water for ultrasonic treatment, then wash it with clean water and ultrapure water for 3 to 5 times respectively, and dry it to constant weight to obtain dry rice husk; (2) Preparation of rice husk carbon: The dry rice husk obtained in step (1) is carbonized to obtain rice husk carbon, and the rice husk carbon is then calcined together with KOH in a tube furnace. The obtained product is treated with hydrochloric acid to remove metal impurities, and washed to neutrality to obtain C / SiO2; (3) Pretreatment of the nanocomposite material: immerse the C / SiO2 obtained in step (2) in an iron salt solution, then add a zinc salt solution, mix the above solution thoroughly by ultrasonication, and then add sodium acetate; (4) Preparation of ZnFe2O4 / C / SiO2 nanocomposite material: The solution obtained in step (3) is subjected to a hydrothermal reaction, and the final product is washed and dried multiple times to obtain a ZnFe2O4 / C / SiO2 nanocomposite material.

2. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: The carbonization step in step (2) is to place the dry rice husk into a porcelain boat and transfer it to a tube furnace for calcination, with nitrogen at 250 ml min -1 The flow rate of nitrogen was continuously flowed into the tube furnace for 1 h to remove air; then the nitrogen flow rate was reduced to 150 ml min -1 , increase the furnace temperature to 700 ℃ at a heating rate of 5 ℃ / min and maintain it for 2 h.

3. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: In step (2), the mass ratio of rice husk carbon to KOH is 1:1; the specific steps of calcination are placing rice husk carbon and KOH in a tube furnace for calcination, and nitrogen is saturated at 250 ml·min -1 The flow rate of nitrogen was continuously allowed to flow into the tube furnace for 1 h to remove air, and then the nitrogen flow rate was reduced to 150 ml min -1 , increase the furnace temperature to 750 ℃ ​​at a heating rate of 5 ℃ / min and hold for 1 h.

4. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: The concentration of the hydrochloric acid in step (2) is 2 mol / L, and the treatment is carried out at a magnetic stirring speed of 500 rpm.

5. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: In step (3), the ratio of C / SiO2 to the iron salt solution is 0.5 g:35 mL; the concentration of the iron salt solution is 8 mol / L, and the iron salt is selected from ferric chloride hexahydrate; the concentration of the zinc salt solution is 4 mol / L, and the zinc salt is selected from zinc chloride.

6. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: The amount of sodium acetate used in step (3) is 3.2 g.

7. The method for preparing the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (4) is 200°C and the reaction time is 15 h.

8. The rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the rice husk-based nanocomposite material ZnFe2O4 / C / SiO2 as claimed in claim 8 in microwave degradation of tetracycline hydrochloride.

10. The use according to claim 9, characterized in that: The dosage of the rice husk-based nano composite material ZnFe2O4 / C / SiO2 is 50-150 mg; the power of the microwave is 100-1000 w.